(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
People often express their thoughts which are evil by utilising superb or intensified excessive exceptional phrases in the text, this type of sentiment is called Sarcasm. While talking, all human beings regularly use intense stress while talking and some gestural clues like moving eyes, movement of hands, etc., to symbolise Sarcasm. These physical gestures are missing in the textual data and making sarcasm dectection very difficult. Due to these difficulties, researchers are showing high interest in detecting Sarcasm in text, mainly in emotion and textual content material. In this project, we detect Sarcasm from both TEXT and EMOTICONS by using the Hadoop MapReduce framework. Sarcasm means one person commenting on other people by using both positive and negative words